2010
DOI: 10.1021/ef9013967
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Melting/Freezing Characteristics of Cu/Paraffin Nanofluid as Phase-Change Material (PCM)

Abstract: A new sort of nanofluid phase-change material (PCM) is developed by suspending a small amount of nanoparticles in melting paraffin. Cu, Al, and C/Cu nanoparticles were selected to add to the melting paraffin to enhance the heat-transfer rate of paraffin. Cu nanoparticles have the best performance for heat transfer. Five dispersants were chosen to make Cu nanoparticles stably suspended in melting paraffin. The nanofluids with Cu nanoparticles show good stability in melting paraffin under the action of Hitenol B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(83 citation statements)
references
References 37 publications
4
72
0
2
Order By: Relevance
“…The two-step method is the most economic method to produce the materials in large scale and has been extensively used to prepare nano-enhanced PCMs [31,[33][34][35][36]. In this method, the ultrasonic vibration technique is usually used to ensure that nanometer-sized materials are well dispersed into the base fluid [33][34][35][36] and appropriate surfactants are used to enhance the stability of nanometer-sized materials in the PCM base fluid to maintain good suspension performance [33,36].…”
Section: Materials Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The two-step method is the most economic method to produce the materials in large scale and has been extensively used to prepare nano-enhanced PCMs [31,[33][34][35][36]. In this method, the ultrasonic vibration technique is usually used to ensure that nanometer-sized materials are well dispersed into the base fluid [33][34][35][36] and appropriate surfactants are used to enhance the stability of nanometer-sized materials in the PCM base fluid to maintain good suspension performance [33,36].…”
Section: Materials Preparationmentioning
confidence: 99%
“…A number of studies have used various nanometer-sized materials to improve the thermal conductivity of paraffin. The dispersion of copper nanoparticles in paraffin was reported by Wu et al [19,34]. Hitenol BC-10 was used as the surfactant.…”
Section: Nano-enhanced Pcms With Paraffin As the Base Fluidmentioning
confidence: 99%
“…The general way to improve thermal conductivity of paraffin PCMs is to add highly thermally-conductive fillers. Metal fillers have good thermal conductivity and, thus, were used often [5][6][7][8][9]. For example, Wu et al [6] reported that by adding 1 wt % Cu nanoparticles into paraffin (Tm = 58-60 • C), the heating and cooling times were reduced by 30.3% and 28.2%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Metal fillers have good thermal conductivity and, thus, were used often [5][6][7][8][9]. For example, Wu et al [6] reported that by adding 1 wt % Cu nanoparticles into paraffin (Tm = 58-60 • C), the heating and cooling times were reduced by 30.3% and 28.2%, respectively. Xiao et al [8] prepared paraffin (Tm = 60-62 • C)/nickel foam and paraffin/copper foam composites by using a vacuum impregnation method.…”
Section: Introductionmentioning
confidence: 99%
“…17 Experiments on the thermophysical properties of nanofluids as phase-change material have been conducted. [18][19][20] Li et al 21 investigated heat transfer characteristics of phase change nano-composite materials for thermal energy storage application. Jia et al 22 investigated solid-liquid phase transition of nanofluids and found that the effect on phase transition time and enthalpy was more significant at low cooling rates than at high cooling rates.…”
Section: Introductionmentioning
confidence: 99%